Unraveling the cytotoxicity and metabolic pathways of binary natural deep eutectic solvent systems - Mbous, Y.P.; Hayyan, M.; Wong, W.F.; Looi, C.Y.; Hashim, M.A. (Nature Publishing Group, 2017)
In this study, the anticancer potential and cytotoxicity of natural deep eutectic solvents (NADESs) were assessed using HelaS3, PC3, A375, AGS, MCF-7, and WRL-68 hepatic cell lines. NADESs were prepared from choline chloride, fructose, or glucose and compared with an N,N-diethyl ethanolammonium chloride:triethylene glycol DES. The NADESs (98 ≤ EC 50 ≥ 516 mM) were less toxic than the DES (34 ≤ EC 50 ≥ 120 mM). The EC 50 values of the NADESs were significantly higher than those of the aqueous solutions of their individual components but were similar to those of the aqueous solutions of combinations of their chief elements. Due to the uniqueness of these results, the possibility that NADESs could be synthesized intracellularly to counterbalance the cytotoxicity of their excess principal constituents must be entertained. However, further research is needed to explore this avenue. NADESs exerted cytotoxicity by increasing membrane porosity and redox stress. In vivo, they were more destructive than the DES and induced liver failure. The potential of these mixtures was evidenced by their anticancer activity and intracellular processing. This infers that they can serve as tools for increasing our understanding of cell physiology and metabolism. It is likely that we only have begun to comprehend the nature of NADESs.